2017
DOI: 10.21273/horttech03784-17
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Economic Contributions and Benefits of Consumer Horticulture

Abstract: Consumer horticulture (CH) programming can result in outcomes and impacts at the individual level, such as money saved by reducing inputs, greater return on the landscape investment, healthier plants, and improved quality of life. It may also lead to community-level impacts that provide public value, such as water quality protection, water conservation, and protection of biodiversity. In addition to documenting such outcomes and impacts, it is important to quantify their economic value, connect the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Indeed, extension's ability to meet public needs for CH relies heavily on volunteer staff (McAleer, 2005;Meyer, 2007), and the EMG volunteer program has the potential to provide ''the largest direct contact service within the Cooperative Extension Service'' (McAleer, 2005). CH programming generates as many or more contacts for extension than other production-focused program areas (Bradley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, extension's ability to meet public needs for CH relies heavily on volunteer staff (McAleer, 2005;Meyer, 2007), and the EMG volunteer program has the potential to provide ''the largest direct contact service within the Cooperative Extension Service'' (McAleer, 2005). CH programming generates as many or more contacts for extension than other production-focused program areas (Bradley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…(Etheredge et al, 2016;Gorman & Cacciatore, 2017;Soga et al, 2017). In many other researches (Etheredge et al, 2016;Bradley et al, 2017;Kelley et al, 2017;Im et al, 2018;Lehmann et al, 2018) there is just a collection of data and information not supported by an appropriate methodological approach. In other cases (Aldous, 2015;Artz, & Davis, 2017), instead, an exact method and excellent results do not correspond to the validity of the study confirmed by the academic community.…”
Section: Fig 3 the Geographical Locations Of The Studiesmentioning
confidence: 99%
“…The horticulture industry provides significant contributions to society, including the provision of healthy foods [1], economic development [2], the provision of essential vitamins and minerals [1], and contributions to recreation and leisure activities [2]. However, the horticulture industry is facing critical challenges globally, which affect the production and processing of and research into horticultural crops [3].…”
Section: Introductionmentioning
confidence: 99%